DAMPAK KERUSAKAN TERHADAP LINGKUNGAN YANG DISEBABKAN OLEH SAMPAH PLASTIK BERDASARKAN TINJAUAN UU NO. 18 TAHUN 2008 - Rafi, Paksi; Nafa Perkasa, Meidyto (Riviera Publishing, 2023)
This journal aims to evaluate the impact of environmental damage caused by plastic waste, with a focus on the legal framework set out in Law No. 18 of 2008. In this journal, the authors analyze the relevance and the effectiveness of the law in dealing with the problem of plastic waste and protect the environment. The research method used in this research is a literature review approach that involves reviewing legal documents, case studies, and related scientific publications. The results of this study indicate that the Law No. 18 of 2008 provides a strong legal framework for waste management plastic. This law provides a clear and firm basis for efforts reduce the negative impact of plastic waste on the environment. Constitution it contains legal requirements, government responsibilities, and mechanisms enforcement aimed at regulating and managing plastic waste effectively. It is hoped that the results of this study can contribute to improving and increase public awareness about the importance of reducing plastic waste is an important step in meeting this challenge. Effective implementation of this law will play a key role in protecting the environment and achieve sustainable plastic waste management.